Method for efficiently detoxifying secondary aluminum ash and synchronously extracting high-purity aluminum oxide

By adopting hydrolysis treatment, alkali calcination and dissolution treatment in secondary aluminum ash, combined with the use of modified calcium oxide powder and glucose, and pulse ultrasonic treatment, alumina in secondary aluminum ash in the prior art was solved. The problems of low extraction rate and low detoxification efficiency have achieved efficient detoxification and high-purity alumina extraction.

CN119430251APending Publication Date: 2025-02-14SOUTH CHINA INST OF ENVIRONMENTAL SCI MEP

Patent Information

Application Number
CN202411570409.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has problems such as low extraction rate, high condition requirements, large energy consumption, large slag discharge and complex operating procedures in the extraction and treatment process of alumina in secondary aluminum ash, and the detoxification efficiency is not high.

Method used

The process flow of hydrolysis treatment, alkaline calcination and dissolution treatment is adopted. By adding modified calcium oxide powder and glucose during the hydrolysis process, combined with pulsed ultrasonic treatment, the efficient detoxication of secondary aluminum ash and the extraction of high-purity alumina are achieved.

Benefits of technology

The removal rate of aluminum nitride in secondary aluminum ash reaches more than 97%, the dissolution rate of aluminum oxide can reach more than 94%, the process flow is simplified, and the energy consumption and slag discharge volume are greatly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430251A_ABST
    Figure CN119430251A_ABST
Patent Text Reader

Abstract

The invention discloses a method for efficiently detoxifying secondary aluminum ash and synchronously extracting high-purity aluminum oxide. The method comprises the following steps: S1, carrying out hydrolysis treatment; s2, roasting treatment; s3, carrying out dissolution treatment; the pulse ultrasonic treatment in the S1 and the S3 is realized through a special pulse ultrasonic device. According to the method, detoxification and efficient extraction of the secondary aluminum ash are achieved through the technological process of hydrolysis, alkaline roasting and dissolution, modified calcium oxide powder and glucose are added in the hydrolysis process, and the combined action can be achieved, so that coating of calcium aluminate wrappage formed in the hydrolysis process of calcium oxide on the surface of aluminum nitride is reduced; further, the hydrolysis effect is improved, aluminum nitride is removed, the removal rate reaches 97% or above, and the dissolution rate of aluminum oxide can reach 94% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary aluminum ash processing, and in particular to a method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide. Background Art

[0002] Secondary aluminum ash is waste generated by the production and processing of aluminum products. It is usually the residue formed by primary aluminum ash in resource recycling, recasting and aluminum smelting. Secondary aluminum ash has complex components and contains toxic and harmful substances. The extraction process is not yet mature, and there are certain limitations in resource recycling. If the secondary aluminum ash is directly landfilled, it will cause environmental pollution and harm to the human body.

[0003] At present, the extraction and treatment processes of alumina in secondary aluminum ash are divided into alkali leaching, acid method, acid-base combined method and alkali sintering method, but they are all unable to be used for industrial production due to low extraction rate, high extraction conditions, high energy and material consumption, large slag discharge volume and complex operation process. Most of the research is still in the experimental stage. Compared with the alkali leaching method, the alkali sintering method uses less alkali and has higher extraction efficiency; compared with the acid leaching method, the alkali sintering method has higher purity of alumina extraction and lower corrosion to instruments; compared with the acid-base combined method, the alkali sintering method has a short process flow and is suitable for industrial production. Therefore, among the above methods, the alkali sintering method is more excellent.

[0004] At the same time, detoxification of secondary aluminum ash is generally carried out by pyrolysis or wet method. Among them, the removal of nitrogen in pyrolysis is mainly due to the reaction of aluminum nitride in aluminum ash with oxygen in the air to form aluminum oxide, which increases the nitrogen removal rate. At the same time, during the reaction, aluminum oxide will slowly coat the surface of aluminum nitride, thereby hindering the further progress of the oxidation reaction. Wet treatment usually adds additives to increase the reaction rate. Calcium oxide as an additive can also promote the hydrolysis and removal of aluminum nitride in secondary aluminum ash, but calcium oxide is easy to form calcium aluminate inclusions during the hydrolysis process, which hinders the smooth progress of the hydrolysis process.

[0005] For example, the invention patent with patent application number CN201910733547.5 discloses a method for recovering high-purity alumina from secondary aluminum ash at the end of regenerated aluminum smelting, comprising the following steps: S1, grinding and screening black ash to obtain fine ash; S2, mixing and stirring the fine ash in S1 with a dissolving agent in a reaction chamber, absorbing the overflowed gas with an ammonia absorption tower, filtering and separating the residue, washing the residue, and mixing the washing liquid into the filtrate for standby use; S3, adding a precipitant to the filtrate, at which time precipitation and gas are generated; S4, adding a purifying agent to the filtrate of S3, adjusting the pH value of the solution to 12-14, filtering and separating the precipitate, washing the precipitate, and mixing the washing liquid into the filtrate for standby use; S5, passing CO2 gas into the filtrate of S4 to generate a precipitate, filtering and separating the precipitate, washing and drying the precipitate; S6, roasting the precipitate in S5 to obtain an alumina product. However, this method also does not solve the above-mentioned problems. Summary of the invention

[0006] In view of the above-mentioned problems, the present invention provides a method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide.

[0007] The technical solution of the present invention is:

[0008] A method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide comprises the following steps:

[0009] S1. Hydrolysis treatment: grind and screen the secondary aluminum ash, mix it with modified calcium oxide powder in a mass ratio of 1:1-1.1, place it in a reaction container to obtain a mixed powder, mix the mixed powder with deionized water and glucose to obtain a primary mixed material, wherein the weight ratio of the mixed powder to deionized water is 1-1.2:10-12, glucose accounts for 0.2-0.4% of the total volume of the primary mixed material, adjust the temperature to 45-50°C, and simultaneously perform pulse ultrasonic treatment for 1.5-2h, and filter to obtain a filter residue;

[0010] S2, roasting treatment: drying the filter residue, mixing it with sodium carbonate powder and sodium hydroxide powder, and then roasting it in a crucible, wherein the weight ratio of the filter residue to the sodium carbonate powder and the sodium hydroxide powder is 1:0.3-0.4:0.5-0.6, the roasting temperature is 800-900° C., and the roasting time is 1.5-2 hours to obtain clinker;

[0011] S3. Dissolution treatment: placing the clinker in a reaction vessel, adding deionized water to obtain a secondary mixed material, and performing dissolution treatment. The dissolution treatment time is 20 to 25 minutes, the dissolution treatment temperature is 60 to 70°C, the weight ratio of clinker to deionized water is 1:13 to 18, and pulse ultrasonic treatment is performed simultaneously. After vacuum filtration and drying, high-purity alumina is obtained.

[0012] Furthermore, the secondary aluminum ash in S1 is ground and sieved and then passed through a 100-mesh sieve, and the modified calcium oxide powder is passed through a 180-mesh sieve.

[0013] Description: By strictly controlling the particle size of secondary aluminum ash and modified calcium oxide powder, sufficient reaction is ensured during hydrolysis and the degree of hydrolysis is improved.

[0014] Furthermore, the preparation method of the modified calcium oxide powder in S1 is: grinding calcium oxide and passing it through a 200-mesh sieve to obtain calcium oxide powder, dispersing the calcium oxide powder in anhydrous ethanol, the weight ratio of calcium oxide powder to anhydrous ethanol is 1:15-20, adding alkyd resin dropwise while stirring, the amount of alkyd resin added is 1-2% of the total mass of the calcium oxide powder, heating to 70-75°C and continuing stirring for 10-12h, filtering, washing, and drying to obtain the modified calcium oxide powder.

[0015] Description: By using modified calcium oxide powder and alkyd resin to hydrophobically modify the surface of calcium oxide, the rapid coating of the aluminum nitride surface by calcium aluminate inclusions that are easily formed during the hydrolysis of calcium oxide can be avoided, thereby improving the hydrolysis and removal of aluminum nitride in secondary aluminum ash.

[0016] Furthermore, in the preparation method of the modified calcium oxide powder, the stirring speed is 100-120 rpm, the dropping speed of the alkyd resin is 2-5 mL / s, the heating rate is 2-4°C / min, anhydrous ethanol is used for washing 2-3 times, and the drying temperature is 45-50°C.

[0017] Furthermore, the drying temperature of the filter residue in S2 is 55-60° C., the sodium carbonate powder and the sodium hydroxide powder are both sieved through a 200-mesh sieve, and the heating rate during roasting is 5-7° C. / min.

[0018] Note: During roasting, the heating rate needs to be reasonably controlled to ensure a stable roasting process.

[0019] Furthermore, during the dissolution treatment in S3, the reaction container is kept sealed and the drying temperature is 55-60°C.

[0020] Furthermore, the pulse ultrasonic treatment in S1 and S3 is achieved by a dedicated pulse ultrasonic device, which is arranged inside the reaction container. The pulse ultrasonic device includes a driving motor fixedly connected to the upper part of the inner wall of the reaction container, a fixing rod is provided at the output end of the driving motor, two support rods are vertically provided at the end of the fixing rod, a waterproof shell is provided at the end of the support rod, an ultrasonic generator is sealed inside the waterproof shell, and an ultrasonic vibration rod is provided at the output end of the ultrasonic generator.

[0021] Description: Ultrasonic waves are applied through a dedicated pulse ultrasonic device to evenly disperse the reaction materials inside the reaction container.

[0022] Furthermore, during the pulse ultrasonic treatment in S1, the powers of the two ultrasonic vibrating rods are set to 200-300W and 300-400W respectively. When the two ultrasonic vibrating rods are kept parallel, they are located above the liquid surface of the primary mixed material. Each time the two ultrasonic vibrating rods rotate into the interior of the mixed material, they pass through at a uniform speed and the passing time is 1-2 minutes. After the two ultrasonic vibrating rods rotate to be parallel, they remain parallel for 30 seconds.

[0023] Description: Pulse ultrasonic treatment is used to partially remove the calcium aluminate inclusions formed on the surface of aluminum nitride, thereby improving the effect of the hydrolysis reaction.

[0024] Furthermore, during the pulse ultrasonic treatment in S3, the powers of the two ultrasonic vibration rods are set to 300-400W and 400-500W respectively, the two ultrasonic vibration rods are located below the liquid surface of the secondary mixed material when they remain parallel, and the height of the ultrasonic vibration rod from the liquid surface is 15-20% of the length of the ultrasonic vibration rod, and the speed of the driving motor is controlled to be 20-30rpm.

[0025] Note: By controlling the two ultrasonic vibrating rods to remain parallel and below the liquid surface of the secondary mixed material, the effect of pulse ultrasound is improved and the dissolution of alumina is promoted.

[0026] The beneficial effects of the present invention are:

[0027] (1) The method of the present invention for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide achieves detoxification and efficient extraction of secondary aluminum ash through a process flow of hydrolysis + alkaline roasting + dissolution. By adding modified calcium oxide powder and glucose during the hydrolysis process, they can work together to reduce the coating of calcium aluminate-like inclusions formed by calcium oxide during the hydrolysis process on the surface of aluminum nitride, thereby improving the hydrolysis effect and achieving the removal of aluminum nitride. The removal rate reaches more than 97%, and the aluminum oxide dissolution rate can reach more than 94%.

[0028] (2) The method of the present invention for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide realizes the application of ultrasonic waves through a dedicated pulse ultrasonic device, thereby uniformly dispersing the reaction materials inside the reaction container, and optimizes the pulse ultrasonic parameters in S1 and S3, and specifically adjusts the pulse ultrasonic combination mode of the hydrolysis reaction, so that the calcium aluminate coating formed on the surface of aluminum nitride is partially detached, thereby improving the effect of the hydrolysis reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a schematic diagram of the aluminum chloride removal rate of each case in Experimental Example 1 of a method for efficient detoxification of secondary aluminum ash and simultaneous extraction of high-purity aluminum oxide of the present invention;

[0030] Figure 2 This is a method for the efficient detoxification of secondary aluminum ash and simultaneous extraction of high-purity aluminum oxide according to the present invention. The schematic diagram of the aluminum oxide dissolution rate of each case in Experimental Example 1;

[0031] Figure 3 This is a schematic diagram of the removal rate of F element in each case of Experimental Example 2 of a method for efficient detoxification of secondary aluminum ash and simultaneous extraction of high-purity aluminum oxide of the present invention;

[0032] Figure 4 This is a front view of the internal structure of the pulsed ultrasonic device in S1 in the method for efficient secondary aluminum ash detoxification and simultaneous extraction of high-purity aluminum oxide of the present invention;

[0033] Figure 5 It is a side view of the internal structure of the pulsed ultrasonic device at S3 in the method for efficient detoxification of secondary aluminum ash and simultaneous extraction of high-purity aluminum oxide of the present invention.

[0034] Among them, 1-driving motor, 2-fixing rod, 3-support rod, 4-waterproof shell, 5-ultrasonic generator, 6-ultrasonic vibration rod. DETAILED DESCRIPTION

[0035] Example 1

[0036] A method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide comprises the following steps:

[0037] S1. Hydrolysis treatment: Grind and screen the secondary aluminum ash, mix it with the modified calcium oxide powder in a mass ratio of 1:1.05, place it in a reaction container to obtain a mixed powder, grind and screen the secondary aluminum ash, pass it through a 100-mesh sieve, and pass the modified calcium oxide powder through a 180-mesh sieve. Mix the mixed powder with deionized water and glucose to obtain a primary mixed material, wherein the weight ratio of the mixed powder to deionized water is 1:10, and glucose accounts for 0.3% of the total volume of the primary mixed material. The temperature is adjusted to 46°C, and pulse ultrasonic treatment is simultaneously performed for 1.75 hours, and filter to obtain a filter residue;

[0038] The preparation method of modified calcium oxide powder is as follows: grinding calcium oxide and passing it through a 200-mesh sieve to obtain calcium oxide powder, dispersing the calcium oxide powder in anhydrous ethanol, wherein the weight ratio of the calcium oxide powder to the anhydrous ethanol is 1:18, adding alkyd resin dropwise while stirring, wherein the amount of alkyd resin added is 1.5% of the total mass of the calcium oxide powder, heating to 73°C and continuing stirring for 11 hours, filtering, washing, and drying to obtain modified calcium oxide powder; wherein the stirring speed is 110 rpm, the dropping speed of the alkyd resin is 3 mL / s, the heating speed is 3°C / min, anhydrous ethanol is used for washing twice, and the drying temperature is 47°C;

[0039] S2, roasting treatment: drying the filter residue, mixing it with sodium carbonate powder and sodium hydroxide powder, and then roasting it in a crucible, the filter residue drying temperature is 58 ° C, the sodium carbonate powder and the sodium hydroxide powder are both sieved through a 200 mesh sieve, the weight ratio of the filter residue to the sodium carbonate powder and the sodium hydroxide powder is 1:0.35:0.55, the roasting temperature is 850 ° C, the roasting time is 1.75h, and the heating rate during roasting is 6 ° C / min to obtain clinker;

[0040] S3, dissolution treatment: placing the clinker in a reaction vessel, adding deionized water to obtain a secondary mixed material, and dissolution treatment, the dissolution treatment time is 22 minutes, the dissolution treatment temperature is 65°C, the weight ratio of clinker to deionized water is 1:15, and pulse ultrasonic treatment is performed simultaneously, the reaction vessel is kept sealed during the dissolution treatment, and high-purity alumina is obtained after vacuum filtration and drying, and the drying temperature is 58°C;

[0041] The pulse ultrasonic treatment in S1 and S3 is achieved by a dedicated pulse ultrasonic device, which is arranged inside the reaction container. The pulse ultrasonic device includes a drive motor 1 fixedly connected to the upper part of the inner wall of the reaction container, a fixed rod 2 is arranged at the output end of the drive motor 1, two support rods 3 are vertically arranged at the end of the fixed rod 2, a waterproof shell 4 is arranged at the end of the support rod 3, an ultrasonic generator 5 is sealed inside the waterproof shell 4, and an ultrasonic vibration rod 6 is arranged at the output end of the ultrasonic generator 5. The drive motor 1, the ultrasonic generator 5 and the ultrasonic vibration rod 6 are all commercially available products;

[0042] During the pulse ultrasonic treatment in S1, the powers of the two ultrasonic vibrating rods 6 are set to 250W and 350W respectively. Figure 4 As shown, when the two ultrasonic vibrating rods 6 are kept parallel, they are located above the liquid surface of the primary mixed material. Each time the two ultrasonic vibrating rods 6 rotate into the interior of the mixed material, they pass through at a uniform speed and the passing time is 1.5 minutes. After the two ultrasonic vibrating rods 6 rotate to be parallel, they remain for 30 seconds.

[0043] During the pulse ultrasonic treatment in S3, the powers of the two ultrasonic vibrating rods 6 are set to 350W and 450W respectively. Figure 5 As shown, the two ultrasonic vibration rods 6 are located below the secondary mixed material liquid surface when they remain parallel, and the height of the ultrasonic vibration rods 6 from the liquid surface is 16% of the length of the ultrasonic vibration rods 6 , and the speed of the driving motor 1 is controlled to be 25 rpm.

[0044] Example 2

[0045] The difference between this embodiment and embodiment 1 is that the specific parameter settings in S1 are different.

[0046] S1. Hydrolysis treatment: Grind and screen the secondary aluminum ash, mix it with modified calcium oxide powder in a mass ratio of 1:1, and place it in a reaction container to obtain a mixed powder. The weight ratio of the mixed powder to deionized water is 1:11, and glucose accounts for 0.2% of the total volume of the primary mixed material. The temperature is adjusted to 45°C, and pulse ultrasonic treatment is performed simultaneously for 1.5 hours, and the filter residue is obtained by filtration.

[0047] Example 3

[0048] The difference between this embodiment and embodiment 1 is that the specific parameter settings in S1 are different.

[0049] S1. Hydrolysis treatment: Grind and screen the secondary aluminum ash, mix it with modified calcium oxide powder in a mass ratio of 1:1.1, and place it in a reaction container to obtain a mixed powder. The weight ratio of the mixed powder to deionized water is 1:12, and glucose accounts for 0.4% of the total volume of the primary mixed material. The temperature is adjusted to 50°C, and pulse ultrasonic treatment is performed simultaneously for 2 hours, and the filter residue is obtained by filtration.

[0050] Example 4

[0051] The difference between this embodiment and embodiment 1 is that the specific parameter settings in S1 are different.

[0052] S1. Hydrolysis treatment: The weight ratio of the mixed powder to deionized water is 1.1:10.

[0053] Example 5

[0054] The difference between this embodiment and embodiment 1 is that the specific parameter settings in S1 are different.

[0055] S1. Hydrolysis treatment: The weight ratio of the mixed powder to deionized water is 1.2:10.

[0056] Example 6

[0057] The difference between this embodiment and embodiment 1 is that the specific parameter settings in S1 are different.

[0058] S1. Hydrolysis treatment: The weight ratio of the mixed powder to deionized water is 1.2:11.

[0059] Note: In Examples 1 to 6, the key influencing parameter for the removal of aluminum nitride is the weight ratio of the mixed powder to deionized water, and the remaining parameters are conventionally adjusted within a reasonable range.

[0060] Example 7

[0061] The difference between this embodiment and embodiment 1 is that the specific parameter settings in S2 are different.

[0062] S2. Calcination treatment: after drying the filter residue, mix it with sodium carbonate powder and sodium hydroxide powder and then place it in a crucible for calcination. The drying temperature of the filter residue is 55°C. Both the sodium carbonate powder and the sodium hydroxide powder are sieved through a 200-mesh sieve. The weight ratio of the filter residue to the sodium carbonate powder and the sodium hydroxide powder is 1:0.3:0.5. The calcination temperature is 800°C. The calcination time is 1.5h. The heating rate during calcination is 5°C / min to obtain clinker.

[0063] Example 8

[0064] The difference between this embodiment and embodiment 1 is that the specific parameter settings in S2 are different.

[0065] S2. Calcination treatment: after drying the filter residue, mix it with sodium carbonate powder and sodium hydroxide powder and then place it in a crucible for calcination. The drying temperature of the filter residue is 60°C. Both the sodium carbonate powder and the sodium hydroxide powder are sieved through a 200-mesh sieve. The weight ratio of the filter residue to the sodium carbonate powder and the sodium hydroxide powder is 1:0.4:0.6. The calcination temperature is 900°C. The calcination time is 2h. The heating rate during calcination is 7°C / min to obtain clinker.

[0066] Note: In Example 1, Example 7 and Example 8, the selected parameters are reasonably selected within the optimal parameter range after experimental verification, and the same technical effect can be achieved by selecting the parameters in any group of embodiments.

[0067] Example 9

[0068] The difference between this embodiment and Embodiment 1 is that the specific parameter settings in S3 are different.

[0069] S3. Dissolution treatment: Place the clinker in a reaction vessel, add deionized water to obtain a secondary mixed material, and perform dissolution treatment. The dissolution treatment time is 20 minutes, the dissolution treatment temperature is 60°C, the weight ratio of clinker to deionized water is 1:13, and pulse ultrasonic treatment is performed simultaneously. Keep the reaction vessel sealed during the dissolution treatment, and obtain high-purity alumina after vacuum filtration and drying at a drying temperature of 55°C.

[0070] Example 10

[0071] The difference between this embodiment and Embodiment 1 is that the specific parameter settings in S3 are different.

[0072] S3. Dissolution treatment: Place the clinker in a reaction vessel, add deionized water to obtain a secondary mixed material, and perform dissolution treatment. The dissolution treatment time is 25 minutes, the dissolution treatment temperature is 70°C, the weight ratio of clinker to deionized water is 1:18, and pulse ultrasonic treatment is performed simultaneously. Keep the reaction vessel sealed during the dissolution treatment, and obtain high-purity alumina after vacuum filtration and drying at 60°C.

[0073] Note: In Example 1, Example 9 and Example 10, the selected parameters are reasonably selected within the optimal parameter range after experimental verification, and the same technical effect can be achieved by selecting the parameters in any group of embodiments.

[0074] Embodiment 11

[0075] The difference between this embodiment and embodiment 1 is that:

[0076] During the pulse ultrasonic treatment in S1, the powers of the two ultrasonic vibrating rods 6 are set to 200W and 300W respectively. When the two ultrasonic vibrating rods 6 are kept parallel, they are located above the liquid surface of the primary mixed material. Each time the two ultrasonic vibrating rods 6 rotate into the interior of the mixed material, they pass through at a uniform speed and the passing time is 1 minute. After the two ultrasonic vibrating rods 6 rotate to be parallel, they remain for 30 seconds.

[0077] During the pulse ultrasonic treatment in S3, the powers of the two ultrasonic vibrating rods 6 are set to 300W and 400W respectively. When the two ultrasonic vibrating rods 6 remain parallel, they are located below the liquid surface of the secondary mixed material, and the height of the ultrasonic vibrating rod 6 from the liquid surface is 15% of the length of the ultrasonic vibrating rod 6. The speed of the driving motor 1 is controlled to be 20rpm.

[0078] Example 12

[0079] The difference between this embodiment and embodiment 1 is that:

[0080] During the pulse ultrasonic treatment in S1, the powers of the two ultrasonic vibrating rods 6 are set to 300W and 400W respectively. When the two ultrasonic vibrating rods 6 are kept parallel, they are located above the liquid surface of the primary mixed material. Each time the two ultrasonic vibrating rods 6 rotate into the interior of the mixed material, they pass through at a uniform speed and the passing time is 2 minutes. After the two ultrasonic vibrating rods 6 rotate to be parallel, they remain for 30 seconds.

[0081] During the pulse ultrasonic treatment in S3, the powers of the two ultrasonic vibrating rods 6 are set to 400W and 500W respectively. When the two ultrasonic vibrating rods 6 remain parallel, they are located below the liquid surface of the secondary mixed material, and the height of the ultrasonic vibrating rod 6 from the liquid surface is 20% of the length of the ultrasonic vibrating rod 6. The speed of the driving motor 1 is controlled to be 30rpm.

[0082] Note: In Example 1, Example 11 and Example 12, the selection of parameters for pulse ultrasonic treatment is related to the amount of secondary aluminum ash to be treated. When the single treatment volume is large, it is more reasonable to select the parameters in Example 12. When the single treatment volume is small, it is more reasonable to select the parameters in Example 11.

[0083] Embodiment 13

[0084] The difference between this embodiment and embodiment 1 is that the parameter settings of the preparation method of the modified calcium oxide powder are different.

[0085] The preparation method of modified calcium oxide powder is as follows: grind calcium oxide and pass it through a 200-mesh sieve to obtain calcium oxide powder, disperse the calcium oxide powder in anhydrous ethanol, the weight ratio of calcium oxide powder to anhydrous ethanol is 1:15, add alkyd resin dropwise while stirring, the amount of alkyd resin added is 1.5% of the total mass of the calcium oxide powder, heat to 70°C and continue stirring for 10 hours, filter, wash and dry to obtain modified calcium oxide powder; wherein, the stirring speed is 100 rpm, the alkyd resin drop speed is 2 mL / s, the heating speed is 2°C / min, anhydrous ethanol is used for washing twice, and the drying temperature is 45°C.

[0086] Embodiment 14

[0087] The difference between this embodiment and embodiment 1 is that the parameter settings of the preparation method of the modified calcium oxide powder are different.

[0088] The preparation method of modified calcium oxide powder is as follows: grind calcium oxide and pass it through a 200-mesh sieve to obtain calcium oxide powder, disperse the calcium oxide powder in anhydrous ethanol, the weight ratio of calcium oxide powder to anhydrous ethanol is 1:20, add alkyd resin dropwise while stirring, the amount of alkyd resin added is 1.5% of the total mass of the calcium oxide powder, heat to 75°C and continue stirring for 12 hours, filter, wash and dry to obtain modified calcium oxide powder; wherein, the stirring speed is 120rpm, the alkyd resin drop speed is 5mL / s, the heating speed is 4°C / min, anhydrous ethanol is used for washing 3 times, and the drying temperature is 50°C.

[0089] Embodiment 15

[0090] The difference between this embodiment and embodiment 1 is that the parameter settings of the preparation method of the modified calcium oxide powder are different.

[0091] The amount of alkyd resin added is 1% of the total mass of calcium oxide powder.

[0092] Example 16

[0093] The difference between this embodiment and embodiment 1 is that the parameter settings of the preparation method of the modified calcium oxide powder are different.

[0094] The amount of alkyd resin added is 2% of the total mass of calcium oxide powder.

[0095] Note: In the preparation process of the modified calcium oxide powder, the parameter adjustments in Example 1, Example 13 and Example 14 are all conventional adjustments within a reasonable range, and the parameter that has a decisive influence on the performance of the modified calcium oxide powder is the amount of alkyd resin added.

[0096] Experimental Example 1

[0097] In order to verify the extraction effect of the method of the present invention on aluminum oxide in secondary aluminum ash, we conducted several groups of indoor tests, respectively using the methods in Examples 1 to 6 for simulation tests and comparing them with the comparative examples. In Comparative Example 1, modified calcium oxide powder was not added, but ordinary calcium oxide powder was used instead; Comparative Example 2 was not added with glucose, and the remaining steps were the same as those in Example 1. The removal rate of aluminum nitride in secondary aluminum ash by hydrolysis and the final dissolution rate of aluminum oxide were analyzed and detected. The results are as follows: Figure 1 and Figure 2 shown.

[0098] like Figure 1 As shown, it can be seen that compared with Example 2 and Example 3, the aluminum nitride removal rate in Example 1 is the highest, indicating that increasing the solid-liquid ratio, that is, the amount of mixed powder, can accelerate the mass transfer of the reaction system, reduce the concentration of the reaction product, and is conducive to the hydrolysis reaction; however, when the solid-liquid ratio, that is, the amount of mixed powder, is further increased in Examples 4 and 5, the viscosity of the primary mixed material increases, the mass transfer becomes worse, and it is not conducive to the hydrolysis reaction. Therefore, the parameters in the preferred embodiment 1 can achieve the optimal aluminum nitride removal rate;

[0099] Compared with Comparative Example 1, the removal rate of aluminum nitride without adding modified calcium oxide powder is significantly reduced. This is because the calcium aluminate inclusions formed during the hydrolysis of calcium oxide are coated on the surface of aluminum nitride, inhibiting further contact between aluminum nitride and water. The modified calcium oxide powder of the present invention can effectively eliminate this problem. At the same time, compared with Comparative Example 2, the removal rate without adding glucose is also slightly reduced. Although the addition of single glucose can also alleviate the formation of calcium aluminate hydration products, the combination of glucose and modified calcium oxide powder can achieve better results.

[0100] like Figure 2 As shown in Figure 2, it can be seen that the final alumina dissolution rate follows the same pattern as Figure 1 This indicates that the removal of aluminum nitride during the hydrolysis process ultimately has a certain impact on the dissolution of aluminum oxide. At the same time, if the aluminum nitride is not completely removed, it will also have an impact on the environment. Therefore, the parameters in Example 1 are preferred.

[0101] Experimental Example 2

[0102] Next, we conducted experiments on the parameters in Example 1, Example 15 and Example 16, mainly analyzing the effect of the amount of alkyd resin added on the performance of the modified calcium oxide powder. At this time, the object of our detection and analysis was the removal rate of the F element, and compared with the comparative example. Among them, the amount of alkyd resin added in Comparative Example 3 was 0.5% of the total mass of the calcium oxide powder, and the amount of alkyd resin added in Comparative Example 4 was 3% of the total mass of the calcium oxide powder.

[0103] like Figure 3 As shown, it can be seen that when the amount of alkyd resin added is gradually increased (Comparative Example 3→Example 15→Example 1), the removal rate of F element in secondary aluminum ash by hydrolysis treatment after the modified calcium oxide powder gradually increases, but when the amount of alkyd resin added continues to increase (Example 1→Example 16→Comparative Example 2), the removal rate of F element in secondary aluminum ash by hydrolysis treatment after the modified calcium oxide powder decreases slightly and then increases slightly, indicating that continuing to increase the amount of alkyd resin added at this time has little effect on the final removal effect of F element, and additionally increases the cost of raw materials. Therefore, the parameter design in Example 1 is preferred.

[0104] Experimental Example 3

[0105] Next, we study the effect of pulse ultrasonic treatment in Example 1, mainly analyzing the influence of pulse ultrasonic treatment on the dissolution rate of aluminum oxide, and comparing it with the comparative examples. In comparative example 5, no ultrasonic treatment is applied, comparative example 6 is subjected to ultrasonic treatment with an ultrasonic power of 300 W, comparative example 7 is subjected to ultrasonic treatment with an ultrasonic power of 400 W, and comparative example 8 is subjected to ultrasonic treatment with an ultrasonic power of 500 W. Finally, the results of the dissolution rate of aluminum oxide in each experimental group are shown in Table 1.

[0106] Table 1 Dissolution rate of aluminum oxide in each experimental group

[0107] Experimental Group Dissolution rate of alumina % Example 1 94.2 Comparative Example 5 90.6 Comparative Example 6 93.3 Comparative Example 7 93.6 Comparative Example 8 93.5

[0108] It can be seen from the data in Table 1 that compared with other experimental groups, the control group has a significantly lower alumina dissolution rate when no ultrasonic treatment is applied. After the ultrasonic treatment is applied, the dissolution rate of alumina is significantly affected, and the continued increase in ultrasonic power has little effect on the dissolution rate of alumina. However, after pulse ultrasonic treatment, the dissolution rate of alumina can be further improved. This may be because the main mechanism of action of ultrasound in assisting the dissolution of alumina is based on the cavitation effect of ultrasound. Ultrasonic cavitation refers to the bubbles generated by ultrasonic waves in the sound transmission medium, which continue to grow, vibrate and finally explode violently. When the pulse acts, the second mixed material locally produces a high temperature and high pressure environment, and this cycle is repeated to release a certain amount of energy, thereby affecting the surrounding substances.

Claims

1. A method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide, characterized in that: The following steps are involved: S1. Hydrolysis treatment: grind and screen the secondary aluminum ash, mix it with modified calcium oxide powder in a mass ratio of 1:1-1.1, place it in a reaction container to obtain a mixed powder, mix the mixed powder with deionized water and glucose to obtain a primary mixed material, wherein the weight ratio of the mixed powder to deionized water is 1-1.2:10-12, glucose accounts for 0.2-0.4% of the total volume of the primary mixed material, adjust the temperature to 45-50°C, and simultaneously perform pulse ultrasonic treatment for 1.5-2h, and filter to obtain a filter residue; S2, roasting treatment: drying the filter residue, mixing it with sodium carbonate powder and sodium hydroxide powder, and then roasting it in a crucible, wherein the weight ratio of the filter residue to the sodium carbonate powder and the sodium hydroxide powder is 1:0.3-0.4:0.5-0.6, the roasting temperature is 800-900°C, and the roasting time is 1.5-2h to obtain clinker; S3. Dissolution treatment: placing the clinker in a reaction vessel, adding deionized water to obtain a secondary mixed material, and performing dissolution treatment. The dissolution treatment time is 20 to 25 minutes, the dissolution treatment temperature is 60 to 70°C, the weight ratio of clinker to deionized water is 1:13 to 18, and pulse ultrasonic treatment is performed simultaneously. After vacuum filtration and drying, high-purity alumina is obtained.

2. The method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity alumina according to claim 1, characterized in that: The secondary aluminum ash in S1 is ground and sieved and then passed through a 100-mesh sieve, and the modified calcium oxide powder is passed through a 180-mesh sieve.

3. The method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity alumina according to claim 1, characterized in that: The preparation method of the modified calcium oxide powder in S1 is as follows: grind calcium oxide and pass it through a 200-mesh sieve to obtain calcium oxide powder, disperse the calcium oxide powder in anhydrous ethanol, the weight ratio of the calcium oxide powder to the anhydrous ethanol is 1:15-20, add alkyd resin dropwise while stirring, the amount of alkyd resin added is 1-2% of the total mass of the calcium oxide powder, heat to 70-75°C and continue stirring for 10-12h, filter, wash and dry to obtain the modified calcium oxide powder.

4. The method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide according to claim 3, characterized in that: In the preparation method of the modified calcium oxide powder, the stirring speed is 100-120 rpm, the dropping speed of the alkyd resin is 2-5 mL / s, the heating speed is 2-4° C. / min, anhydrous ethanol is used for washing 2-3 times, and the drying temperature is 45-50° C.

5. The method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity alumina according to claim 1, characterized in that: The drying temperature of the filter residue in S2 is 55-60° C., the sodium carbonate powder and the sodium hydroxide powder are both sieved through a 200-mesh sieve, and the heating rate during roasting is 5-7° C. / min.

6. The method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide according to claim 1, characterized in that: During the dissolution treatment in S3, the reaction container is kept sealed and the drying temperature is 55-60°C.

7. The method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide according to claim 1, characterized in that: The pulse ultrasonic treatment in S1 and S3 is achieved by a dedicated pulse ultrasonic device, which is arranged inside the reaction container and comprises a drive motor (1) fixedly connected to the upper part of the inner wall of the reaction container, a fixed rod (2) being provided at the output end of the drive motor (1), two support rods (3) being vertically provided at the end of the fixed rod (2), a waterproof shell (4) being provided at the end of the support rod (3), an ultrasonic generator (5) being sealed inside the waterproof shell (4), and an ultrasonic vibration rod (6) being provided at the output end of the ultrasonic generator (5).

8. The method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide according to claim 7, characterized in that: During the pulse ultrasonic treatment in S1, the powers of the two ultrasonic vibration rods (6) are set to 200-300W and 300-400W respectively. When the two ultrasonic vibration rods (6) are kept parallel, they are located above the liquid surface of the primary mixed material. Each time the two ultrasonic vibration rods (6) rotate into the interior of the mixed material, they pass through at a uniform speed and the passing time is 1-2 minutes. After the two ultrasonic vibration rods (6) rotate to be parallel, they remain parallel for 30 seconds.

9. The method for efficiently detoxifying secondary aluminum ash and simultaneously extracting high-purity aluminum oxide according to claim 7, characterized in that: During the pulse ultrasonic treatment in S3, the powers of the two ultrasonic vibration rods (6) are set to 300-400W and 400-500W respectively, the two ultrasonic vibration rods (6) are located below the liquid surface of the secondary mixed material when they are kept parallel, and the height of the ultrasonic vibration rod (6) from the liquid surface is 15-20% of the length of the ultrasonic vibration rod (6), and the rotation speed of the driving motor (1) is controlled to be 20-30rpm.

Citation Information

Patent Citations

  • A method for recovering high-purity alumina from secondary aluminum ash at the end of recycled aluminum smelting.

    CN110436498B

Cited By

  • Method for preparing high-purity aluminum oxide from secondary aluminum ash based on calcium peroxide activation

    CN122562000A